Investigation of the parameters affecting the release of flurbiprofen from chitosan microspheres - Müşerref Günseli Yüksel Tilkan; Nurten Özdemir (Universidade de São Paulo, 2018)
ABSTRACT Flurbiprofen (FLB), a NSAID, widely used for preventing pain generally for arthritis or dental problems. In this study, FLB loaded chitosan microspheres were prepared by ionotropic gelation method. In this method, microspheres were formed by dropping chitosan solutions containing FLB into sodium alginate solutions including sodium tripolyphosphate (TPP). A variety of formulation parameters like drug:polymer ratio, drug concentration, polymer's molecular weight, polymer concentration, pH and the concentration of TPP solutions, drying method and stirring time were analyzed. The dissolution studies were performed in a shaking water bath in pH 7.4 phosphate buffer saline (PBS) at 37 °C. Laser diffractometer was used for particle size analysis, and scanning electron microscope (SEM) was used for morphological properties. Drug loading and loading efficiency were calculated by using UV spectrophotometer. The particles obtained were spherical with 0.7-1.3 mm size range, and the loading efficiency was approximately 21-79%. The dissolution studies conducted revealed that drug:polimer ratio and the polymer type and concentration affected the drug release from microspheres. It was observed that increasing the polymer concentration, polymer's molecular weight and TPP concentration decreased the FLB release from microspheres, which was according to Higuchi kinetics.